Paddy farmers' sustainability practices in granary areas in Malaysia - Mohamed, Zainal Abidin; Terano, Rika; Shamsudin, Mad Nasir; Abd. Latif, Ismail (MDPI, 2016)
Food safety is a serious concern among the consumers of agricultural products. Toxicity risks are created by the acute presence of contaminating chemicals in foods. The usage of chemical inputs in paddy farms has not only caused health issues for farmers but it has also adversely affected the environment, killed animals, and polluted air and water. This creates controversial issues that need immediate attention, since sustainable agriculture needs to meet both consumers’ and farmers’ welfare in terms of food and farmers’ safety, respectively. This study looks at paddy farming practices and the creation of the Farmer Sustainability Index as a measurement to gauge whether farmers are practicing sustainable agriculture by following the Rice Check guideline that has been stipulated by the Department of Agriculture, Malaysia. The questionnaire was constructed to capture the 16 farming practices based on the Rice Check guideline and a score was given to each practice to see whether the guideline is being followed. The data from the questionnaire were analyzed and the Farmer Sustainability Index was calculated. The range of index is from 0 to 100, where 0 is not sustainable at all and 100 is highly sustainable. Eighty (80) paddy farmers from Sungai Petani, Kedah participated in the study and the result shows that 80% of the farmers practice quite unsustainable paddy farming with an average score of less than 40.0 on a scale of 0–100.